1998
DOI: 10.1029/97jd02612
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry in biomass burning plumes and implications for tropospheric ozone over the tropical South Atlantic

Abstract: Abstract. Photochemistry occuring in biomass burning plumes over the tropical south Atlantic is analyzed using data collected during the Transport and Atmospheric Chemistry Near the Equator-Atlantic aircraft expedition conducted during the tropical dry season in September 1992 and a photochemical point model. Enhancement ratios (AY/AX, where A indicates the enhancement of a compound in the plume above the local background mixing ratio, Y are individual hydrocarbons, CO, 03, N20, HNO3, peroxyacetyl nitrate (PAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
236
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(267 citation statements)
references
References 59 publications
25
236
6
Order By: Relevance
“…Model studies have also found that limiting fire emissions to the boundary layer underestimates their influence in downwind regions (Cook et al, 2007;Freitas et al, 2007;Brioude et al, 2009;Chen et al, 2009;Jian and Fu, 2014). More effort is needed to evaluate model simulation of ozone production from biomass burning emissions, in particular during the evolution of fire plumes and over regions that are dominated by biomass burning emissions (e.g., Mauzerall et al, 1998;Alvardo et al, 2010;Singh et al, 2010;Arnold et al, 2015).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…Model studies have also found that limiting fire emissions to the boundary layer underestimates their influence in downwind regions (Cook et al, 2007;Freitas et al, 2007;Brioude et al, 2009;Chen et al, 2009;Jian and Fu, 2014). More effort is needed to evaluate model simulation of ozone production from biomass burning emissions, in particular during the evolution of fire plumes and over regions that are dominated by biomass burning emissions (e.g., Mauzerall et al, 1998;Alvardo et al, 2010;Singh et al, 2010;Arnold et al, 2015).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…This enhancement ratio is in the range of that calculated in Pfister et al (2006), of approximately 0.26 ppbv/ppbv downwind of the 2004 fires. Mauzerall et al (1998) reported different O 3 / CO ratios depending on the age of the air mass ranging from 0.15 to 0.74 for fresh to aged plumes during the TRACE-A experiment. While CO is emitted from fires, O 3 is produced from the fire-emitted precursors as the air mass moves downstream.…”
Section: Relationship Between Ozone and Comentioning
confidence: 99%
“…Another limitation is that the technique cannot be used if cloud cover inhibits the satellite AOD measurements. Also the smoke must dissipate out of the defined active region (where the fires are burning) before the trace-gas-to-AOD ratios change significantly as a result of the different atmospheric lifetimes of the various components: (hours for NH 3 and H 2 CO; days for the particulate matter that causes elevated AOD; 1 -2 months for CO and approximately 3 months for HCN) [Li et al, 2000;Mauzerall et al, 1998]. …”
Section: Paton-walsh Et Al: Forest Fire Emissions Inferred From Aod mentioning
confidence: 99%